2018
DOI: 10.1002/smtd.201700367
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical Assessment of Pulmonary Surfactant Predicts the Lung Toxicity of Nanomaterials

Abstract: With the rapid development of nanotechnology and an increasing use of nanoenabled consumer products, there is an urgent need to develop precautionary tools to evaluate acute lung toxicity of engineered nanomaterials (ENMs). As natural pulmonary surfactant (PS) film represents the initial barrier of nano–bio interactions in the lungs, a novel in vitro experimental method, called constrained drop surfactometry (CDS), is developed to quantitatively evaluate PS inhibition caused by ENMs. The results show that at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 33 publications
0
34
0
Order By: Relevance
“…This is particularly important because several studies have shown that particles can interact with fluid layers, altering their composition, lateral organization, and physico-chemical properties, especially the rheological one [15][16][17][18][19]. Therefore, the understanding of the interaction of particles with lung surfactant models is particularly important because it can help to deepen the potential impact of inhaled particles on the properties of this system, which may be useful as a preliminary tool for the evaluation of the potential toxicity of inhaled particles [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is particularly important because several studies have shown that particles can interact with fluid layers, altering their composition, lateral organization, and physico-chemical properties, especially the rheological one [15][16][17][18][19]. Therefore, the understanding of the interaction of particles with lung surfactant models is particularly important because it can help to deepen the potential impact of inhaled particles on the properties of this system, which may be useful as a preliminary tool for the evaluation of the potential toxicity of inhaled particles [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…It is worth mentioning that the Langmuir monolayer of such lipid does not allow accounting for the re-spreading processes, occurring during expiration, of the material squeezed out from the interface during inspiration, which requires considering the role of two of the surface active proteins of the lung surfactant (mainly the surface proteins B, SP-B, and C, SP-C) [13,[39][40][41][42]. However, DPPC Langmuir monolayers can be considered as a good tool for a preliminary evaluation of the worsening of the physico-chemical properties of lung surfactant layers as a result of the incorporation of solid particles, even though the biophysical relevance of these studies may be rather limited [23,43].…”
Section: Introductionmentioning
confidence: 99%
“…As opposed to aerosolizing ZnO NPs, others have mixed LS with ZnO NPs to evaluate the effect of LS function 30,31 also using the constrained drop surfactometer. Yang et al 31 studied the interaction of LS with several NPs, among which ZnO (mixed with the natural LS extract Infasurf to a final concentration of 10 µg/mg LS, or 1.2 cm 2 /mg).…”
Section: Discussionmentioning
confidence: 99%
“…The effects observed in the present study are much more severe at a lower exposure dose, where we observe an increase in minimum surface tension increases from 5.5 ± 0.6 to 13.8 ± 1.8 mN/m (n = 5) upon exposure, as opposed to an increase from 2.5 to 4.0 mN/m in the study by Yang et al 31 Yang et al showed that the rise of the minimum surface tension of Infasurf after exposure to ZnO NPs was directly correlated to alveolar collapse seen in histology and inflammation observed after intratracheal installation in mice. 30…”
Section: Discussionmentioning
confidence: 99%
“…hydrophobic nanomaterials bind relatively more to phospholipids than hydrophilic nanomaterials [134]. A wide range of nanomaterials have been shown to affect the function of lung surfactant in vitro including metal and carbon-based nanomaterials [135][136][137][138][139][140][141][142][143].…”
Section: Aop 302 Lung Surfactant Function Disruption Leading To Acutementioning
confidence: 99%